2003
DOI: 10.1002/erv.529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adolescent body satisfaction and associated eating disorder pathology in two communities

Abstract: Objective: As Eastern European countries adopt Anglo-American ideals of body size, it can be predicted that body dissatisfaction (a core feature of the eating disorders) will be similar to that observed in western cultures. The objective of the present investigation is to compare adolescent males and females in urban schools of two countries (Scotland and Yugoslavia) as part of an ongoing longitudinal study of BMI, body satisfaction, well-being and eating pathology. Method: 625 adolescents had their BMI record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
2
9
0
1
Order By: Relevance
“…Assim, na literatura, as abordagens sobre a imagem corporal não são homogéneas sendo que, por vezes, cada aspeto teórico é considerado isoladamente como parte da imagem corporal (Akdemir et al, 2012;Baranowksi et al, 2003;Kakeshita & Almeida, 2006;Najam & Ashfaq, 2012). Outras vezes, esses componentes são tratados, equivocadamente, como sinónimo de imagem corporal (Costa & Vasconcelos, 2010;Miranda, Filgueiras, Neves, Teixeira, & Ferreira, 2012).…”
Section: Métodounclassified
“…Assim, na literatura, as abordagens sobre a imagem corporal não são homogéneas sendo que, por vezes, cada aspeto teórico é considerado isoladamente como parte da imagem corporal (Akdemir et al, 2012;Baranowksi et al, 2003;Kakeshita & Almeida, 2006;Najam & Ashfaq, 2012). Outras vezes, esses componentes são tratados, equivocadamente, como sinónimo de imagem corporal (Costa & Vasconcelos, 2010;Miranda, Filgueiras, Neves, Teixeira, & Ferreira, 2012).…”
Section: Métodounclassified
“…Until recently, most research on body image in adolescents has focused on young women's concerns with body fat. For young women the presence of elevated body fat is viewed as a deviation from the thin ideal body type and so they are more likely to judge themselves as fat despite they may be normal weight or even underweight, reporting body image dissatisfaction (8, 12,36,(54)(55)(56)(57)(58).…”
Section: Differences In Body Image Dissatisfaction Between Males and mentioning
confidence: 99%
“…Some limitations of the use of the Figure Rating Scale is that they do not distinguish between fat deposition and increased muscle mass as the cause of an increase in body size. If a person is dissatisfied and would like to be more muscular, it may be apparent that the larger figures look "fatter" as opposed to muscular, whereas the slimmer silhouettes may actually be perceived as being more toned, derived to the inability of these silhouette's to make a muscle/fat distinction (43,58). Other potential problem is that the sizes and dimensions reflected by the figures may not match of individual clients, leading individuals to say "none of these shapes look like me" (24).…”
Section: Depressive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the problem of body dissatisfaction and eating disorders was thought to be the problem of Western societies [6]. However, several studies [7][8][9] have clearly demonstrated that body dissatisfaction and disordered eating is leading to serious psychological and nutritional consequences in Asia.…”
Section: Introductionmentioning
confidence: 99%